Transnational Organized Crime and its Perspectives in Conditions of Global Instability - M. E. Khachatryan; M. M. Shumilov (Евразийская интеграция: экономика, право, политика, 2019)
The article examines transnational organized crime, the ways of it’s classification, its types and subjects. The characteristic of directions, where crime groups have their activities. Also there is a complex of reasons of development of international crime, the solving of which could increase the level of the global security.